Has China achieved carbon emission reduction through pilot free trade zones? - Hao, Xiaomin; Wang, Haiping (Frontiers in Environmental Science, 2025)
With the continuous improvement of China’s openness, pilot free trade zones (FTZs) have played an increasingly prominent role in promoting low-carbon transformation. A thorough exploration of the impact of FTZs development on regional low-carbon growth holds significant theoretical and practical value for advancing high-quality green economic development. Based on panel data from 285 prefecture-level cities in China from 2009 to 2022, this study empirically examines the impact of FTZs establishment on regional carbon emission reduction and its underlying mechanisms. The results show that FTZs development has a significant positive effect on regional green and low-carbon transformation. However, this effect exhibits heterogeneity depending on geographical location and industrial structure, with FTZs in coastal regions and those dominated by the tertiary sector demonstrating a more pronounced contribution to carbon reduction. Further analysis reveals that the promotion of green and low-carbon transformation by FTZs is primarily achieved through three key pathways: facilitating green technological innovation, enhancing industrial agglomeration, and optimizing green finance. Based on the research findings, this paper puts forward the following recommendations to promote green development: leveraging green policies to guide the green transformation of industries; adopting region-specific strategies to advance differentiated regional green development; fostering high-quality green development through technological innovation and diversified approaches; and strengthening green risk management to safeguard both economic and ecological security.